STUDENTS VS. LANGUAGE: CHALLENGES FACED BY THE UNDERGRADUATES OFFERING ENGLISH MEDIUM INSTRUCTION IN SRI LANKA - J., Kennedy (PEOPLE: International Journal of Social Sciences, 2017)
This study verifies the challenges faced by the undergraduate students who offer English Medium Instruction (EMI) whose mother tongue is other than English where the English language is taught as second language. After the independence, Sri Lanka continued with the same system to its educational sector until the late 1950’s in the school level. But in the tertiary level, the natural science based subjects continued to confine to the English Medium Instruction. This trend has been expanded to other field of studies in the tertiary level such as social sciences and humanities. Currently, as in the case of other countries – especially the Asian countries, Sri Lanka also switched to EMI not only in the tertiary level but also in the secondary level of education as well. Concerning the tertiary level of education, a higher level of language proficiency is expected for a successful academic study in the EMI where this would be a platform for the language development. This study was conducted among a group of weaker students in English language skills those who failed in the General English courses in the first year of study in their under graduation who are at present in their second year of study. This study reveals that more than 70% of the students would like to switch on again to have their course of study to L1 though they realize the importance of the English language.